Paramedics, technicians, and survival from out of hospital cardiac arrest. Issue 5 (September 1997) - Rainer, T H; Marshall, R; Cusack, S
Abstract : OBJECTIVE: To test the hypothesis that limited paramedic advanced life support skills afford no advantage in survival from cardiac arrest when compared with non-paramedic ambulance crews equipped with defibrillators in an urban environment; and to investigate whether separate response units delayed on scene times. METHODS: A prospective, observational study was conducted over 17 consecutive months on all adult patients brought to the accident and emergency (A&E) department of Glasgow Royal Infirmary having suffered an out of hospital cardiac arrest of cardiac aetiology. The main interventions were bystander cardiopulmonary resuscitation (CPR) and limited advance life support skills. MAIN OUTCOME MEASURES: Return of spontaneous circulation, survival to admission, and discharge. RESULTS: Of 240 patients brought to the A&E department, 19 had no clear record of whether a paramedic was or was not involved and so were excluded. There was no difference in survival between the two groups, although a trend to admission favoured non-paramedics. Paramedics spent much longer at the scene (P < 0.0001). Witnessed arrests (P = 0.01), early bystander CPR (P = 0.12), shockable rhythms (P = 0.003), and defibrillation (P < 0.0001) were associated with better survival. Intubation and at scene times were not associated with better survival. Delayed second response units did not prolong at scene times. CONCLUSIONS: The interventions of greatest benefit in out of hospital cardiac arrest are basic life support and defibrillation. Additional skills are of questionable benefit and may detract from those of greatest benefit.